Digital Literacy As A Media Guide Amid Digital Disruption (Study of The Importance of Digital Literacy in The Era of Globalization) - Syaifudin Zuhri; Rozaqul Arif (Jurnal Indonesia Sosial Teknologi, 2024)
The rapid development of information and communication technology (ICT) in the last 15 years has made people aware of digital technology is importance in life. However, the impact of this technology has created an "information tsunami" on a large scale, even an explosion of information explosions (information explosions) at any time. It spreads widely without knowing boundaries, space and time, so that people often get confused about which information is correct and which is false. Hoax, which one can educate and which one plunges. This research wants to explore the urgency of digital media literacy in dealing with the flood of information amidst the ongoing digital disruption. Media and digital literacy can be used as an approach that focuses on critically analyzing media content and the right way to behave. When the Internet presented a variety of new media platforms, the era of media convergence occurred; literacy is very important for society because it can be a guide (guide) in behaving, including selecting and analyzing any information received from digital media. In this study, researchers used a qualitative descriptive method, using a literature study method, because this research is intended to explore the phenomenon of the development of digital literacy as one of the new challenges in today's era. This article is intended to provide an understanding of digital literacy, so it is hoped that it can be useful as a contribution to knowledge about community empowerment in the era of globalization.